Kryminalizacja pośrednictwa ubezpieczeniowego w prawie karnym gospodarczym - Ochman, Piotr; Solecki, Sebastian (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The subject of the article is the analysis of criminal laws criminalizing insurance intermediation in Poland. This is an issue that falls under the dogmatic considerations of criminal economic law in the aspect of protecting the statics of economic turnover, i.e. its basic structures and institutions. The evolution of the criminalization of this sector of the insurance market, the genesis of current criminal law regulations as well as critical remarks to the latest penal provisions of the Insurance Distribution Act will be presented. The analyzes will be the basis for presenting de lege lata’s comments and the de lege ferenda proposal.
Keywords: pośrednictwo ubezpieczeniowe; prawo gospodarcze; prawo karne gospodarcze